Total assets versus risk weighted assets: Does it matter for MREL? - Bennet Berger; Pia Hüttl; Silvia Merler (Bruegel, 2016)
The European Union's Bank Recovery and Resolution Directive foresees a "minimum requirement for own funds and eligible liabilities" (known as MREL) that banks need to comply with in order to ensure the effectiveness of the bail-in tool. The details of how MREL should be constructed in practice are under discussion. We look at alternative ways to compute MREL, showing how the choice of the benchmark metric (risk weighted assets, total assets or leverage exposure) can change the allocation of requirements across banks. We also review MREL in light of the global effort to ensure future resolvability of banks, highlighting some differences with, and inconsistencies in relation to, the Financial Stability Board's total loss-absorption capacity (TLAC) measure.
Keywords: 330